A study of reverse osmosis reject water at Bukit Gambir, Tangkak Haemodialysis Centre - A. Hamid, Hazren; Harun, Hasnida; Mohamed Sunar, Norshuhaila; Ahmad, Faridahanim; Hamidon, Nuramidah; Muhamad, Mimi Suliza; Salahuddin, Nor Areena (Penerbit UTHM, 2020)
Water is categorized by their few aspects according to the specific feature and it function usage in a certain compatible condition. Yet with rapidly population growth increasing around the world by about 85 million per year, the accessibility for fresh water supply per persons keep declining [1]. The increasing clean water demand causes the increasing environmental risks, costs and economic exploitation as it may disturb surrounding nature which leads into the more distant sources or greater depth. At this state, the minimization of waste water produce should be focused on to prevent it become worsen.